1965
DOI: 10.1139/v65-468
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Constituents: Xxix. The Essential Oil of Marihuana: Composition of Genuine Indian Cannabis Sativa L.

Abstract: The essential oil obtained by hydrodistillation of freshly harvested Indian Cannabis sativa L. \vas found to contain the following constituents that have not previously been reported: or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

1969
1969
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 9 publications
2
18
0
1
Order By: Relevance
“…These results agree with those of Nigam et al ., (1965) who found the first two plus α‐selinene as major compounds in the essential oil distillates of an Indian variety of C. sativa . The most complete compilation of Cannabis essential oil components was presented by Turner et al .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results agree with those of Nigam et al ., (1965) who found the first two plus α‐selinene as major compounds in the essential oil distillates of an Indian variety of C. sativa . The most complete compilation of Cannabis essential oil components was presented by Turner et al .…”
Section: Resultssupporting
confidence: 94%
“…1, Scheme 1) indicate that the variance is mainly of a quantitative nature apart from the specific pollen volatiles. Nigam et al . (1965) found that the essential oil compositions from male and female were ‘almost identical’.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with cannabinoid derivatives, the volatile constituents of cannabis have received much less attention. Nevertheless, the chemical composition of the volatile fraction of cannabis derived products is well documented and has been mainly established through the analysis of their essential oils [16][17][18][19][20][21][22][23][24][25] or by means of headspace sampling techniques [25][26][27][28][29]. Hence, a large variety of volatile compounds representing all chemical classes (hydrocarbons, alcohols, ketones, esters) have been detected in cannabis samples [20].…”
Section: Headspace Sampling Of Volatile Constituentsmentioning
confidence: 99%
“…这 些 化 合 物 包 括 反 式 -β-金 合 欢 烯 (trans-β-farnesene, 1) [2] 、化合物 2 和异莪术呋喃二烯 (isofuranodiene, 3) [3] . 其中化合物 2 为新化合物, 依据该 化合物的核磁数据, Gavagnin 小组提出它的结构如图 1 所 示 , 与 苍 术 酮 (atractylon, 4) [4] 和 1,2-dihydrotubipofuran (5)类似 [5] , 都是桉烷(eudesmane)倍半萜类天然产 物; 但对应于化合物 2 的天然产物的绝对构型尚无法确 定.…”
unclassified